THE ANXIETY THAT CONVEYING TRAGEDY IN OTHELLO DRAMA BY SHAKESPEARE - Maharani, Puja; Arianto, Tomi (BASIS (Bahasa dan Sastra Inggris), 2022)
Humans are always in touch with the needs in this life. In order to survive, one of the most important examples is the need for safety needs. The phenomenal drama Othello by Shakespeare was chosen as the main data source in this research. This research aimed to analyze the unfulfilled of safety needs in the form of anxiety and its impact on the main character in Shakespeare's drama "Othello". This drama was set in 1603 with a tragedy and was written by the world-famous playwright William Shakespeare. The story that ended in tragedy is inseparable from the anxiety used by others to overthrow power and the Othello family. With these problems, the researchers explored the anxiety factor by using Maslow's psychological theory about the hierarchy of needs, especially at the level of safety needs. This research used qualitative descriptive method because the data collection technique used is to describe the analysis through words and sentences that exist in the data source. The approach used in this research was psychological approach in a literary work. The results found from this research that there is an anxiety factor that underlie Othello's feeling that he is always threatened. Jealousy is a factor that causes anxiety in the character "Othello" which focused on household relationships. This excessive anxiety then causes impacts in the form of misunderstanding, the death of Othello's wife, and Othello's suicide.